The Core Gospel On Restoring the Crux of the Matter - Love, Bill (Abilene Christian University Press, 1992)
This book offers summaries of preaching from generations of ministers within the Stone-Campbell tradition and Churches of Christ more specifically. The Core Gospel is divided into three sections: Part One: The Core Gospel in the New Testament; Part Two: Our Restoration Proclamation of the Core Gospel; Part Three: Current Preaching of the Core Gospel (in the 1990s). This book offers one-of-a-kind synopses of preachers and preaching, and is an important source of data on religious life through more than five generations of Christians.